Birth Preparedness and Complication Readiness among Women Attending Antenatal Clinics in Ogbomoso, South West, Nigeria - Ajibola Idowu, MBBS, FWACP; Samson Ayo Deji, MBChB, MPH, FWACP; Olatayo Ayodele Aremu, MBBS, FWACP; Olumuyiwa Matthew Bojuwoye, MBBS, FMCP; Akinyemi David Ofakunrin, MBBS, FMCPed (Global Health and Education Projects, Inc., 2015)
Background: Information on factors associated with birth preparedness and complication readiness (BP/CR) is central in designing cost effective programs for reducing maternal deaths among women. This study assessed factors influencing BP/CR among pregnant women attending antenatal clinic in Ogbomoso, South West Nigeria. Methodology: This is a cross-sectional study conducted between January and April, 2015. Systematic sampling technique was employed to recruit 400 women attending antenatal clinic at Bowen University Teaching Hospital, Ogbomoso, Nigeria. A pre-tested questionnaire was used for data collection and data analysis was done using SPSS version 21. Chi-square test was used for bivariate analysis while binary logistic regression was used for multivariate analysis. Statistical significance was set at p <0.05. Results: More than half (51.3%) of our respondents were in the 30-39 age category. Only 40.3% of these respondents were reported well prepared for births and were complication ready. The proportion of women who had BP/CR was significantly higher among those in the middle socio-economic group (51.6%, p<0.05), those who practiced Christianity (76.4%, p<0.05) and those from Yoruba ethnic group (80.1%, p<0.05). Respondents in lower socio-economic group were 42% less likely to have prepared for birth compared to women in the high socio-economic class (OR: 0.58, 95% CI: 0.34-0.99). Conclusion and Global Health Implications: The proportion of Nigerian women in our sample who were well-prepared for birth and its complication was below average. There is need for more awareness programs on BP/CR; such programs should target all women especially the vulnerable group. Key words: Birth Preparedness • Complication Readiness • Antenatal Care • Maternal Mortality • Nigeria • Focused Antenatal Care • Demographic and Health Survey Copyright © 2015 Idowu et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.